Reading Ursula Bowlby’s Letters (1939-1940): A Chronicle of First Time Motherhood - Ross, Lynda R. (Journal of the Motherhood Initiative for Research and Community Involvement, 2014)
Drawing on the correspondence Ursula Bowlby wrote to John Bowlby following thebirth of their first child, Mary Hamilton, this paper explores Ursula’s experience with motherhood in the context of pre-War Britain. Not withstanding Ursula’s privileged position in British society, her expressed views and feelings about mothering are in many ways both timeless and classless. Ursula’s experiences of motherhood are also significant since her husband was to become the world’s leading ‘expert’ on attachment and a staunch advocate for mothers as primary attachment figures and selfless participants in childrearing. Ursula’s letters provide a chronicle of the ordinary experiences of motherhood. Juxtaposed to the formidable influence that ‘attachment theory’ was to have in defining motherhood, her letters reveal what little influence her lived experiences had on her husband’s theoretical writings on the subject.